Direct Writing Large‐Area Multi‐Layer Ultrasmooth Films by an All‐Solution Process: Toward High‐Performance QLEDs. (3rd November 2020) - Zhang, Min; Deng, Huanhuan; Meng, Lili; Wang, Hongqin; Wang, Yunjun; Liu, Huan
Abstract: With increasing the film area/layer, deteriorating in both smoothness and uniformity of thin‐films frequently happen, which remains a barrier for making large‐area quantum dot light‐emitting diodes (QLEDs) by solution processes. Here, we demonstrated a facile all‐solution process guided by the conical fiber array to write multi‐layer ultrasmooth thin‐films directly in centimeter scale. The side‐by‐side fibrous array helps to align surface tensions at the tri‐phase contact line to facilitate large‐area homogeneous deposition, which was verified by theoretical simulation. The Laplace pressure along individual conical fiber contributes to the steady liquid transfer. Thin‐films with small roughness (<2.03 nm) and large‐area (2×2 cm 2 ) uniformity were prepared sequentially on the target substrate, leading to large‐area high‐performance QLEDs. The result offers new insights for fabricating large‐area high‐performance thin‐film devices. Abstract : Large‐area multi‐layer ultrasmooth thin‐films were fabricated by an all‐solution process in a direct‐writing manner guided by a conical fiber array. Thin‐films with small roughness (<2.03 nm) and large‐scale (2×2 cm 2 ) uniformity were prepared in sequence on the same target substrate, based on which a large‐area high‐performance QLED with an external quantum efficiency of 15.02 % was fabricated.